Runtime Verification of .NET Contracts - Barnett, Mike; Schulte, Wolfram (The Journal of Systems and Software, 2003)
We propose a method for implementing behavioral interface specifications on the .NET platform. Our interface specifications are expressed as executable model programs. Model programs can be run either as stand-alone simulations or used as contracts to check the conformance of an implementation class to its specification. We focus on the latter, which we call runtime verification.In our framework, model programs are expressed in the new specification language AsmL. We describe how AsmL can be used to describe contracts independently from any implementation language, how AsmL allows properties of component interaction to be specified using mandatory calls, and how AsmL is used to check the behavior of a component written in any of the .NET languages, such as VB, C#, or C++.